Microbial richness and composition independently drive soil multifunctionality - Delgado-Baquerizo, Manuel; Trivedi, Pankaj; Trivedi, Chanda; Eldridge, David J.; Reich, Peter B.; Jeffries, Thomas C.; Singh, Brajesh K. (Functional ecology, 2017)
Soil microbes provide multiple ecosystem functions such as nutrient cycling, decomposition and climate regulation. However, we lack a quantitative understanding of the relative importance of microbial richness and composition in controlling multifunctionality. This knowledge gap limits our capacity to understand the influence of biotic attributes in the provision of services and functions on which humans depend. We used two independent approaches (i.e. experimental and observational), and applied statistical modelling to identify the role and relative importance of bacterial richness and composition in driving multifunctionality (here defined as seven measures of respiration and enzyme activities). In the observational study, we measured soil microbial communities and functions in both tree‐ and bare soil‐dominated microsites at 22 locations across a 1,200 km transect in southeastern Australia. In the experimental study we used soils from two of those locations and developed gradients of bacterial diversity and composition through inoculation of sterilized soils. Microbial richness and the relative abundance of Gammaproteobacteria, Actinobacteria, and Bacteroidetes were positively related to multifunctionality in both the observational and experimental approaches; however, only Bacteroidetes was consistently selected as a key predictor of multifunctionality across all experimental approaches and statistical models used here. Moreover, our results, from two different approaches, provide evidence that microbial richness and composition are both important, yet independent, drivers of multiple ecosystem functions. Overall, our findings advance our understanding of the mechanisms underpinning relationships between microbial diversity and ecosystem functionality in terrestrial ecosystems, and further suggest that information on microbial richness and composition needs to be considered when formulating sustainable management and conservation policies, and when predicting the effects of global change on ecosystem functions. A plain language summary is available for this article. Plain Language Summary